ANALISIS BUTIR SOAL UJIAN AKHIR SEMESTER (UAS) BAHASA JERMAN KELAS X MIA 6 SMA NEGERI 1 MAOSPATI TAHUN PELAJARAN 2015/2016 - MELINDA FEBRIANI, IRENA (LATERNE, 2016)
Evaluation of learning is the last activity purposed to know how far learning objectives are accomplished. Evaluation help the teacher to measure and assess student?s learning progress. Test as a measurement device to be expected capable of giving true information that can be recognized the truth. A good test must contain good validity, reliability, interpretation, practical use and the effectifity of each question which include level of difficulty (item difficulty) and good item discrimination. Analysis of question item is needed because we will know how good the each question item difficulty and the item discrimination too, it is because not all of the question item contains a good question item difficulty and item discrimination. The formuliation of the problem in this reasearch is: 1) How good the question item difficulty of the Deutch final examination test of student class X MIA 6 SMA Negeri 1 Maospati. 2) How good the question item discrimination of the Deutch final examination test of student class X MIA 6 SMA Negeri 1 Maospati. 3) how good the multiple choice distractor answer of the Deutch final examination test of student class X MIA 6 SMA Negeri 1 Maospati. The purpose of this reaserch is: 1) To describe the question item difficulty of the Deutch final examination test of student class X MIA 6 SMA Negeri 1 Maospati. 2) To describethe question item discrimination of the Deutch final examination test of student class X MIA 6 SMA Negeri 1 Maospati. 3) To describe how good the multiple choice distractor answer of the Deutch final examination test of student class X MIA 6 SMA Negeri 1 Maospati. This research is a quantitative analysis research. Quantitative analysis in this research is for analyze question item difficulty, question item discrimination, and the multiple choice answer distractor using IF (Item Facility) and ID (Item Discrimination) formula. From this research we know from 40 question item 21 or 52,5% item is worthy to use and the other 19 item or 47,5% is not worthy to use or needs improvement, to be inspected again. And almost all the multiple choice answer distractor is not working well either because 142 or 83%. Diferent in the test set B, from 40 question item 16 or 40% item is not worthy to use and the other 24 item or 60%item is worthy to useor needs improvement, to be inspected again. Altrnative answers on a matter of test B also need to be considered because 142 item or 83% the multiple choice answer distractor in not working well. Key wort : quetion item analysis, question item dificulty, question item discrimination